Prediction Of Electrostatic Discharge Soft Error On Two-Way Radio Using Simulation And Immunity Scanning Technique - Antong, Rosnah (2017)
Electrostatic discharge (ESD) is a major cause of failures and malfunctions in two-way communication radio. Soft error failures like logic error, latch-up and wrong reset can occur as a result of the excessive ESD. It is a well-known fact that the Complementary Metal-Oxide- Semiconductor (CMOS) devices are more susceptible to ESD. The failure of CMOS ICs due to ESD can also cause radio to reset or shutdown completely. Presently the failures are detected after the radio is built and tested only. In this research, new methodology is developed to assess the ESD risk of two-way radio at circuit level. Poynting vector is used to calculate the incident power received by susceptible integrated circuit during ESD. In doing so the two-way radio is modeled in 3-D using the IEC 61000-4-2 standard. The result provides a graphical means to visualize the propagation of ESD current in Printed Circuit Board (PCB) and ground plane. Time-weighted average power density (Stwa) calculated as a cross product between E-field and H-field was used extensively in the modeling, from which a maximum limit of 3.7 W=m2, Stwa was established for predicting ESD failures. It was observed that results obtained through computer simulation agree well with measured values within some tolerance limit. It was also discovered that the improved radio with metal bar is well above this limit compared to the original radio. It is also predicted that the soft error due to ESD would occur at 11 kV and 8 kV for improved and original radio respectively. Results from this study provide a new scheme for engineers to assess ESD risk of two-way radio at PCB level. Identifying most susceptible component to ESD allows radio failures to be addressed adequately before mass production.